Anomalous nonlinear optical effect and enhanced emission by magnetic excitons in CVD grown cobalt-doped ZnSe nanoribbon. (11th March 2021) - Zou, Bingsuo; Hou, Lipeng; Tian, Ye; Han, Junbo; Peng, Hui; Yang, Xiongtao; Shi, Lijie
Abstract: The magnetic excitons in diluted magnetic semiconductor (DMS) have varied formats due to the inhomogeneous phases out of doping concentration and/or structural relaxations or defects. Here the high quality cobalt-doped zinc blende ZnSe nanoribbons (NRs) were synthesized, showing bright and color-variable emissions from blue, yellow to a little mixed white colors. Their power and temperature dependent micro-photoluminescence (PL) spectra have been obtained in which two emission bands, one magnetic exciton band near the band-edge and a Co 2+ high-level d – d transition emission band at 550 nm out of their ferromagnetic (FM) coupled aggregates in ZnSe lattice, both bands could also be reflected by a nonlinear optical absorption enhancement. The easy formed stacking fault defects in a chemical vapor deposition (CVD) grown ZnSe zincblende NR took part in the above optical processes out of magnetic polaronic excitons (PXs). The femtosecond (fs) laser pulse pumping on single ZnSe:Co NR produces obvious lasing behavior but with profile of a complicated magnetic exciton interactions with indication of a crossover from collective exciton magnetic polarons (EMP) to bound magnetic polaron (BMP) scattering in Co doped ZnSe NR. These findings indicate the complication of the magnetic coupling natures in varied DMS structures, whose optical properties have been found to be highly nonlinear, due to the involvement of the spin–spin, spin–exciton and spin–phonon interactions, verified by the theoretic calculation in Yang X-T et al (2019 Interstitial Zn-modulated ferromagnetism in Co-doped ZnSe Mater. Res. Express 6 106121).